2000
DOI: 10.1016/s0014-5793(00)01436-8
|View full text |Cite
|
Sign up to set email alerts
|

F‐ATPase: specific observation of the rotating c subunit oligomer of EFoEF1

Abstract: The rotary motion in response to ATP hydrolysis of the ring of c subunits of the membrane portion, F o , of ATP synthase, F o F 1 , is still under contention. It was studied with EF o EF 1 (Escherichia coli) using microvideography with a fluorescent actin filament. To overcome the limited specificity of actin attachment through a Cys-maleimide couple which might have hampered the interpretation of previous work, we engineered a`strep-tag' sequence into the C-terminal end of subunit c. It served (a) to purify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(127 citation statements)
references
References 34 publications
9
118
0
Order By: Relevance
“…During ATP synthesis, a mechanical rotation of the γ-subunit driven by the transmembrane proton-motive force, exerted on a ring of C-subunits in the F o membrane domain of the intact enzyme, takes each of the three β-subunits in its catalytic domain through the states represented by the β TP -, β DP -, and β Esubunits, thereby synthesizing three ATP molecules during each 360°rotation (1,11). Hydrolysis of ATP reverses the direction of rotation, and protons are ejected from the mitochondrial matrix into the intermembrane space through the F o domain of the enzyme (12,13). The rotation of the γ-subunit is not continuous, but it proceeds in 120°steps consisting of 90°and 30°substeps (14).…”
mentioning
confidence: 99%
“…During ATP synthesis, a mechanical rotation of the γ-subunit driven by the transmembrane proton-motive force, exerted on a ring of C-subunits in the F o membrane domain of the intact enzyme, takes each of the three β-subunits in its catalytic domain through the states represented by the β TP -, β DP -, and β Esubunits, thereby synthesizing three ATP molecules during each 360°rotation (1,11). Hydrolysis of ATP reverses the direction of rotation, and protons are ejected from the mitochondrial matrix into the intermembrane space through the F o domain of the enzyme (12,13). The rotation of the γ-subunit is not continuous, but it proceeds in 120°steps consisting of 90°and 30°substeps (14).…”
mentioning
confidence: 99%
“…Previous work that showed rotation of the c subunit ring by using fluorescent actin filament technology failed to provide evidence of this. Pänke et al (27) did not measure the effect of F 1 F ospecific inhibitors on their observed rotation of the c subunit ring. Sambongi et al (25) examined the effect of venturicidin, but their results have shown very little inhibition by this potent reagent.…”
Section: Discussionmentioning
confidence: 97%
“…1B; refs. [25][26][27]. However, none of these studies were conducted with fully functional enzyme because in each case, the F 1 F o being used no longer showed a significant sensitivity to the inhibitors generally used to show that the F 1 F o ATP synthase is coupled (26,28).…”
mentioning
confidence: 99%
“…An actin filament connected to the c ring rotated upon ATP hydrolysis and generated similar torque to that observed for the g rotation . A similar experiment was carried out using a different method to connect the actin probe to the c ring (Pänke et al 2000). Experimental systems for observing rotation were critically discussed Wada et al 2000).…”
Section: Rotational Catalysis Of F-atpasementioning
confidence: 99%